PENGARUH INTERNAL CORPORATE SOCIAL RESPONSIBILITY DAN EMPLOYEE ENGAGEMENT TERHADAP EFEKTIVITAS KERJA PERAWAT DI RUMAH SAKIT HARAPAN SEHAT SLAWI - Yudia Mahardika; Arlette Arlette; Yuniati Lestari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
Nurse is very important in the implementation of health services in hospitals. In reality, there are many problems related to work effectiveness, especially for nurses in Indonesia. The problem of nurse work effectiveness by existing internal corporate social responsibility. Another factor of work effectiveness problem of nurses by low employee engagement. The purpose of this study to determine the effect of internal corporate social responsibility and employee engagement on nurses work effectiveness at RS. Harapan Sehat Slawi. This study using quantitative method, sample size is 52 respondents. The data analysis technique is multiple linear regression analysis. The significance value of the t-test on Internal Corporate Social Responsibility towards work effectiveness was 0.000 (t-value was 3.978). The significance value of the t-test on Employee Engagement towards work effectiveness is 0.006 (t-value is 4.520). The calculated F value is 16.382 with a significance level of 0.000. The conclusion of this study is that Internal corporate social responsibility has a positive and significant influence to nurse work effectiveness, Employee engagement has a positive and significant influence to nurses work effectiveness, Internal corporate social responsibility and employee engagement simultaneously have a positive and significant influence to nurses work effectiveness in RS. Harapan Sehat Slawi.